OPTIMASI UNIT PLTU BERBAHAN BAKAR BATUBARA MENGGUNAKAN METODE LAGRANGE DI PT. INDONESIA POWER UP SURALAYA - Murti, A.S.; Manuaba, I.B.G.; Arjana, I.G.D (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i01.p11, 2020)
The magnitude of the need for a load, the characteristics of a plant, the max and min limits of generating capacity, as well as the expenditure for fuel for each generating unit economically influences the operation of the plant. The purpose of this research is to obtain the minimum generation cost in a certain loading conditions on the power system by the Lagrange multiplier. Loading data used are data on May 14, 2018 at 07.00 WIB. The final results show that, with a total generation of 2644 MW, the costs must be incurred in the amount of Rp1,180,776,616.22 while the lagrange method used to optimize the plant, the cost of generation is Rp1,160,220,968.97. The amount of savings that can be done for one hour is 07.00 WIB which is Rp. 20,555,647.26. From the studies that have been carried out it can be concluded that the Lagrange method is able to produce a minimum generation cost which is quite good compared to the cost of real generation.